Human development report 2016 : human development for everyone - United Nations Development Programme (UNDP) (New York : United Nations Publications, 2016)
This publication explores how work can enhance human development, given that the world's workforce is changing rapidly, and even with progress, significant human development challenges still remain. It takes a broad view of going beyond jobs and examines the linkage between work and human development.
CHAPTER 1. Human development--achievements, challenges and hopes ---- CHAPTER 2. Universalism--from principles to practice ---- CHAPTER 3. Reaching everyone--analytical and assessment issues ---- CHAPTER 4. Caring for those left out--national policy options ---- CHAPTER 5. Transforming global institutions ---- CHAPTER 6. Human development for everyone--looking forward.
Includes bibliographical references.
AAL
Devalopment Bool Agency
Keywords: Economic development -- Social aspects; Quality of life; Industries -- Social aspects; Work -- Health aspecs